2021
DOI: 10.1016/j.dcn.2021.100968
|View full text |Cite
|
Sign up to set email alerts
|

Sexually dimorphic development in the cortical oscillatory dynamics serving early visual processing

Abstract: Highlights Visual processing dynamics continue to develop throughout childhood and adolescence. Visual alpha response power differed between males and females. Sex and age interacted to modulate visual gamma responses. Peak frequency predicted response power above and beyond the effects of age and sex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Given the smaller, somewhat imbalanced sample size, we were limited in the breadth and depth of analyses we were able to perform, including explorations of sex-specific changes in neural oscillatory dynamics over time. Several recent studies have shown unique trajectories of development among male versus female youths in investigations of both task-based ( Fung et al, 2021 ; Taylor et al, 2021 , 2020 ) and spontaneous cortical dynamics ( Ott et al, 2021 ). Future longitudinal studies should aim to acquire data from larger samples of equally-balanced male and female youths to further disentangle the unique trajectories of fluid reasoning maturation in this dynamic period of development.…”
Section: Discussionmentioning
confidence: 99%
“…Given the smaller, somewhat imbalanced sample size, we were limited in the breadth and depth of analyses we were able to perform, including explorations of sex-specific changes in neural oscillatory dynamics over time. Several recent studies have shown unique trajectories of development among male versus female youths in investigations of both task-based ( Fung et al, 2021 ; Taylor et al, 2021 , 2020 ) and spontaneous cortical dynamics ( Ott et al, 2021 ). Future longitudinal studies should aim to acquire data from larger samples of equally-balanced male and female youths to further disentangle the unique trajectories of fluid reasoning maturation in this dynamic period of development.…”
Section: Discussionmentioning
confidence: 99%
“…We also tested whether these trajectories differed between sexes, as males and females show divergent biological variations, for instance in brain volume (25,26) and functional network connectivity (27). Some studies report sex differences in MEG (28)(29)(30)(31) or EEG features (32)(33)(34)(35)(36)(37) during or in absence of a task in various age ranges and frequencies. However, research efforts in this direction for the resting-state are generally limited.…”
Section: Introductionmentioning
confidence: 99%
“…We also tested whether these trajectories differed between sexes, as males and females show divergent biological variations, for instance in brain volume (Ritchie et al, 2018; Ruigrok et al, 2014) and functional network connectivity (Satterthwaite et al, 2015). Some studies report sex differences in MEG (Azanova et al, 2021; Fung et al, 2021; Hoshi & Shigihara, 2020; Taylor et al, 2020) or EEG features (Brenner et al, 1995; Clarke et al, 2001; Davidson et al, 1976; Kober & Neuper, 2011; Smit et al, 2008; Thordstein et al, 2006) during or in absence of a task in various age ranges and frequencies. However, research efforts in this direction for the resting-state are generally limited.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, previous work has found alpha, beta, and gamma each to be important in mediating perception and attention, particularly in the parietal cortex ( Misselhorn et al, 2019 , Zaretskaya and Bartels, 2015 ). Specifically, during this developmental period, increases in theta activity have been reported during abstract reasoning ( Taylor et al, 2020 ) and selective attention performance ( Taylor et al, 2021 ), age-related changes in visual gamma activity have been seen during basic visual processing ( Fung et al, 2021 ), alterations in alpha activity have been reported during verbal working memory processing ( Embury et al, 2019 , Killanin et al, 2022 ), and beta and gamma oscillations have been found to change in relation to a developing sensorimotor system ( Heinrichs-Graham et al, 2018 , Trevarrow et al, 2019 , Wilson et al, 2010 ). In the current study, beta and gamma activity increased with increasing DHEA in posterior parietal and occipital regions of the brain, which are in line with roles in attention and early sensory processing.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a previous study using MEG elucidated age- and sex-related effects in spontaneous neural dynamics in adolescents across specific canonical frequency bands ( Ott et al, 2021 ). In addition, several prior MEG studies have shown that task-related neural oscillatory dynamics are sensitive to critical indicators of development, including pubertal testosterone, and that this developmental sensitivity is modulated by sex ( Fung et al, 2020 , Fung et al, 2021 , Killanin et al, 2020 , Taylor et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%